One-step synthesis of quaternized silica nanoparticles with bacterial adhesion and aggregation properties for effective antibacterial and antibiofilm treatments. Issue 16 (25th March 2022) - Yang, Jing; Zhu, Ya-Xuan; Lu, Pengpeng; Zhu, Baofeng; Wu, Fu-Gen
Abstract : Quaternized silica nanoparticles with excellent bacterial adhesion and aggregation properties are prepared for effective antibacterial and antibiofilm treatments. Abstract : Preservation of the intact cell morphology of bacteria is recognized as one important cause of bacterial drug resistance, and hence developing new antibacterial agents capable of fighting against bacteria via disrupting their cell envelope is highly desirable. Herein, by adopting a modified Stöber method, we developed a one-step approach to fabricate quaternized silica nanoparticles (NPs) using two commercially available molecules—a long alkyl chain-bearing quaternary ammonium silane compound, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (Si-QAC), and tetraethyl orthosilicate (TEOS). Specifically, small spherical quaternized silica NPs with an average size of ∼34 nm could be prepared at a TEOS/Si-QAC molar ratio of 4 : 1 with a very high yield (>90%), and the resultant NPs (termed TS4 NPs) possessed superb colloidal stability (at least 520 d) and good biocompatibility. In addition, we confirmed that the long alkyl chain (C18 )-bearing quaternary ammonium group endowed the TS4 NPs with the capacity to efficiently kill negatively charged Gram-positive bacteria via both hydrophobic and electrostatic interactions. Specifically, the TS4 NPs could coat the Staphylococcus aureus ( S . aureus ) cells via densely binding to the bacterial surface and induce the formation of TS4– S . aureus aggregates to exert their membrane disruption and reactive oxygen species (ROS) production effects, leading to the breakage of intracellular DNA and bacterial death. Besides, we revealed that TS4 could eradicate the mature S . aureus biofilms and inhibit the formation of S . aureus biofilms. The present work proposes a simple one-step method to prepare quaternized silica NPs with excellent bacterial adhesion and aggregation properties, which will find practical applications to fight against infections caused by bacteria and their biofilms.